Seagrass (Zostera marina) Colonization Promotes the Accumulation of Diazotrophic Bacteria and Alters the Relative Abundances of Specific Bacterial Lineages Involved in Benthic Carbon and Sulfur Cycling - Sun, Feifei; Zhang, Xiaoli; Zhang, Qianqian; Liu, Fanghua; Zhang, Jianping; Gong, Jun (Applied and Environmental Microbiology, 2015)
Seagrass colonization changes the chemistry and biogeochemical cycles mediated by microbes in coastal sediments. In this study, we molecularly characterized the diazotrophic assemblages and entire bacterial community in surface sediments of a Zostera marina -colonized coastal lagoon in northern China. Higher nitrogenase gene ( nifH ) copy numbers were detected in the sediments from the vegetated region than in the sediments from the unvegetated region nearby. The nifH phylotypes detected were mostly affiliated with the Geobacteraceae , Desulfobulbus , Desulfocapsa , and Pseudomonas . Redundancy analysis based on terminal restriction fragment length polymorphism analysis showed that the distribution of nifH genotypes was mostly shaped by the ratio of total organic carbon to total organic nitrogen, the concentration of cadmium in the sediments, and the pH of the overlying water. High-throughput sequencing and phylogenetic analyses of bacterial 16S rRNA genes also indicated the presence of Geobacteraceae and Desulfobulbaceae phylotypes in these samples. A comparison of these results with those of previous studies suggests the prevalence and predominance of iron(III)-reducing Geobacteraceae and sulfate-reducing Desulfobulbaceae diazotrophs in coastal sedimentary environments. Although the entire bacterial community structure was not significantly different between these two niches, Desulfococcus ( Deltaproteobacteria ) and Anaerolineae ( Chloroflexi ) presented with much higher proportions in the vegetated sediments, and Flavobacteriaceae ( Bacteroidetes ) occurred more frequently in the bare sediments. These data suggest that the high bioavailability of organic matter (indicated by relatively lower carbon-to-nitrogen ratios) and the less-reducing anaerobic condition in vegetated sediments may favor Desulfococcus and Anaerolineae lineages, which are potentially important populations in benthic carbon and sulfur cycling in the highly productive seagrass ecosystem.